Sustainable development of human resources in a globalization period - Shaikh, Erum 1988-; Tunio, Muhammad Nawaz 1984- (IGI Global, 2022)
This book offers chapters to understand what kind of human resource management strategies and practices organizations should adopt for the sustainability of their organization, exploring different strategies for the betterment, welfare, and smooth running of the organization.